2016
DOI: 10.1161/hcq.0000000000000018
|View full text |Cite|
|
Sign up to set email alerts
|

2016 ACC/AHA Clinical Performance and Quality Measures for Adults With Atrial Fibrillation or Atrial Flutter

Abstract: The American Heart Association requests that this document be cited as follows: Heidenreich PA, Solis P, Estes NAM 3rd, Fonarow GC, Jurgens CY, Marine JE, McManus DD, McNamara RL. 2016 ACC/AHA clinical performance and quality measures for adults with atrial fibrillation or atrial flutter: a report of the American College of Cardiology/American Heart Association Task Force on Performance Measures. Circ Cardiovasc Qual Outcomes. 2016;9:443-488. DOI: 10.1161/HCQ.0000000000000018. This article has been copublis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 123 publications
0
15
0
Order By: Relevance
“…Although not all measures are developed with the intention for integration into Medicare programs, there still exists an opportunity for stakeholders to advocate for inclusion of these validated measures into CMS’ quality programs. For example, such measures include the American Academy of Neurology’s “Patient/Caregiver Nutritional Preferences” [ 28 ] and “Patient Counseled About Advanced Health Care Decision-Making, Palliative Care, or End-Of-Life Issues,” [ 29 ] the American College of Cardiology/American Heart Association’s “SDM Between Physician and Patient in Anticoagulation Prescription Prior to Discharge” [ 30 ] and “SDM Between Physician and Patient in Anticoagulation Prescription,” [ 30 ] and the Society for Interventional Radiology’s “Communication and SDM with Patients and Families for Interventional Oncology Procedures” [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although not all measures are developed with the intention for integration into Medicare programs, there still exists an opportunity for stakeholders to advocate for inclusion of these validated measures into CMS’ quality programs. For example, such measures include the American Academy of Neurology’s “Patient/Caregiver Nutritional Preferences” [ 28 ] and “Patient Counseled About Advanced Health Care Decision-Making, Palliative Care, or End-Of-Life Issues,” [ 29 ] the American College of Cardiology/American Heart Association’s “SDM Between Physician and Patient in Anticoagulation Prescription Prior to Discharge” [ 30 ] and “SDM Between Physician and Patient in Anticoagulation Prescription,” [ 30 ] and the Society for Interventional Radiology’s “Communication and SDM with Patients and Families for Interventional Oncology Procedures” [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…With warfarin, physicians recommend dose control, frequent monitoring, and bleeding assessment when prescribing concomitant drugs, such as NSAIDs. 13 32 Although NOACs may increase the risk of bleeding events, the use of NOACs is suggested in guidelines, and there is insufficient evidence about interactions with concomitant drugs. 13 For these reasons, physicians may have given less attention to the risk of concomitant drugs in prescribing NOACs, and they need to consider concomitant drugs when prescribing NOACs.…”
Section: Discussionmentioning
confidence: 99%
“…Patient perceptions of the burdens and benefits of anticoagulation are important in the context of AF management, since treatment is generally life‐long, often requires behavior change (ie, change in diet), and is associated with potential harm. In addition to their associations with clinical outcomes, assessment of patient beliefs and preferences surrounding anticoagulation is a critical component of anticoagulation shared decision making, a process endorsed for providers and patients by the 2016 American College of Cardiology AF Quality Guidelines . In parallel with increasing recognition of its importance, treatment satisfaction has become increasingly integrated into health care research …”
Section: Discussionmentioning
confidence: 99%
“…In addition to their associations with clinical outcomes, assessment of patient beliefs and preferences surrounding anticoagulation is a critical component of anticoagulation shared decision making, a process endorsed for providers and patients by the 2016 American College of Cardiology AF Quality Guidelines. 28 In parallel with increasing recognition of its importance, treatment satisfaction has become increasingly integrated into health care research. 29 We observed that visual impairment, depression, and anxiety were independently associated with higher self-reported burden of anticoagulation among elderly participants with AF.…”
Section: Discussionmentioning
confidence: 99%